Everolimus, a mammalian target of rapamycin inhibitor, ameliorated streptozotocin-induced learning and memory deficits via neurochemical alterations in male rats - Fanoudi, Sahar; Hosseini, Mahmoud; Alavi, Mohaddeseh Sadat; Boroushaki, Mohammad Taher; Hosseini, Azar; Sadeghnia, Hamid R. (Technische Universität Dortmund, 2018)
Everolimus (EVR), as a rapamycin analog, is a selective inhibitor of the mammalian target of rapamycin (mTOR) kinase and its associated signaling pathway. mTOR is a serine/threonine protein kinase and its hyperactivity is involved in the pathophysiology of Alzheimer’s disease (AD) and associated cognitive deficits. The present study evaluated the impact of EVR, on cognitive functions, hippocampal cell loss, and neurochemical parameters in the intracerebroventricular streptozotocin (icv-STZ) model of AD rats. EVR (1 and 5 mg/kg) was administered for 21 days following the single administration of STZ (3 mg/kg, icv) or for 7 days on days 21-28 post-STZ injection after establishment of cognitive dysfunction. Cognitive deficits (passive avoidance and spatial memory), oxidative stress parameters, acetylcholinesterase (AChE) activity, and percentage of cell loss were evaluated in the hippocampus. Chronic administration (1 and 5 mg/kg for 21 days from the day of surgery and icv-STZ infusion) or acute injection (5 mg/kg for 7 days after establishment of cognitive impairment) of EVR significantly attenuated cognitive dysfunction, neuronal loss, oxidative stress and AChE activity in the hippocampus of STZ-AD rats. In conclusion, our study showed that EVR could prevent or improve deteriorations in behavioral, biochemical and histopathological features of the icv-STZ rat model of AD. Therefore, inhibition of the hyperactivated mTOR may be an important therapeutic target for AD.
EXCLI Journal;Vol. 17 2018
Keywords: Everolimus; mTOR; Alzheimer’s disease (AD); Oxidative stress; Acetylcholinesterase; Streptozotocin; 610